The improvement of collaborative networks to increase small and medium enterprises (SMEs) performance - Mulyana, Mulyana; Wasitowati, Wasitowati (Serbian Journal of Management, 2021)
This study aims to examine the effect of collaborative networks on business performance. This study tries to find a collaborative network format that can improve business performance. The respondents in this study were 295 owners of the fashion sector SMEs in Central Java, Indonesia. Data analysis used the Structural Equation Modeling (SEM) approach. The results showed that collaborative networks (CN) significantly influence innovation capability (IC), competitive advantage (CA), and business performance (BP). Furthermore, the capability of innovation and competitive advantage also significantly influence business performance. Innovation capabilities and competitive advantages can mediate the relationship between collaborative networks and business performance.